Associação entre contexto acadêmico, sono e percepção subjetiva de estresse em estudantes universitários em período pandêmico: 24h-Mesyn Study - Azevedo, Jacyara Christina Carvalho (Universidade Federal do Tocantins, 2025)
Objective: To examine whether there is an association between sleep, academic context and perceived stress in university students during the COVID-19 pandemic. Methods: This is a cross-sectional study that evaluated 195 university students (68.7% female; 44.6% aged between 21 and 25 years old; 65.8% enrolled in health sciences; 24.5% enrolled in the 1st to the 3rd semester). Data was collected in the first half of 2021. We collected measures online using the Perceived Stress Scale (14 items) and the Pittsburgh Sleep Quality Index (19 items). We evaluated the scores of the positive and negative stress dimensions as outcomes (representing the perception of self-efficacy and helplessness). In addition, we also adopted shift, schedule, number of classes enrolled and hours of study per day; and, habitual sleep time (hours per night) and routine (waking up and sleeping) as exposures. We examined associations using multilevel linear regression. Results: In our study, we did not observe a relationship between the academic context, and sleep duration and routine with the positive domain of perceived stress. On the other hand, we observed that the number of classes enrolled (β = 0.73 [95% CI 0.20 to 1.26]) and bedtime (β = -0.11 [95% CI -0.17 to -0.04]) were associated with the negative dimension of perceived stress. Conclusion: The number of classes enrolled and bedtime were associated with perceived helplessness, resulting in increased perceived stress in university students from low-income regions during the COVID-19 pandemic.